Analysis of adult neurogenesis in transgenic mouse models for Zeb1 - Gupta, B.; Berx, G.; Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc; Siebzehnrubl, F. A. (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

A Necessary Role for Cyclin D2 Induction During Colon Cancer Progression Mediated by L1 - Saha, Arka; Gavert, Nancy; Brabletz, Thomas; Ben-Ze’ev, Avri (Cells, 2024)
The cell adhesion molecule L1CAM (L1), mainly known for its function in brain cells, is a Wnt/β-catenin signaling target gene in colorectal cancer (CRC) cells, where it promotes invasion and liver metastasis. We interrogated which genes are expressed at increased levels in human CRC tissue and induced in CRC cell lines overexpressing L1. We found increased cyclin D2 levels in CRC tissue and LS 174T and HCT 116 human CRC cells overexpressing L1. Increased cyclin D2 in CRC cells was associated with higher proliferation rates, faster motility, tumorigenesis, and liver metastasis. The suppression of cyclin D2 expression by shRNA to cyclin D2 blocked the increase in these cellular properties of L1-expressing cells. The overexpression of cyclin D2 in the absence of L1 also conferred tumorigenic properties similar to L1 expression. The pathways involved in the elevation of cyclin D2 by L1 include NF-κB, Akt, and β-catenin signaling but not the Erk pathway. We found that in a significant percentage of human CRC tissue samples, cyclin D2 is expressed at high levels in the nuclei of cancer cells. At the same time, the adjacent normal mucosa was negative for cyclin D2 staining. The results suggest that the increased cyclin D2 expression by L1 is required to induce proliferative, motile tumor development in CRC tissue and can serve as a diagnostic marker and a target for CRC therapy.
CRIS-Team Scopus Importer:2024-11-22
Keywords: colon cancer; cyclin D2; invasion and liver metastasis; L1

A necessary role for increased biglycan expression during L1‐mediated colon cancer progression - Saha, Arka; Cheriyamundath, Sanith; Kumar, Anmol; Gavert, Nancy; Brabletz, Thomas; Ben‐ze’ev, Avri (International Journal of Molecular Sciences, 2022)
Aberrant activation of Wnt/β‐catenin signaling and downstream β‐catenin‐TCF target genes is a hallmark of colorectal cancer (CRC) development. We identified the immunoglobulin‐like cell adhesion receptor L1CAM (L1) as a target of β‐catenin‐TCF transactivation in CRC cells. Overexpression of L1 in CRC cells confers enhanced proliferation, motility, tumorigenesis, and liver metastasis, and L1 is exclusively localized at invasive areas of human CRC tissue. Several genes are induced after L1 transfection into CRC cells by a mechanism involving the L1‐ezrin‐NF‐κB pathway. We conducted a secretomic analysis of the proteins in the culture medium of L1‐overexpressing CRC cells. We detected a highly increased level of biglycan, a small leucine‐rich ECM component, and a signaling molecule. We found that induction of biglycan is required for the cellular processes conferred by L1, including enhanced proliferation, motility, tumorigenesis, and liver metastasis. The suppression of endogenous biglycan levels or a point mutation in the L1 ectodomain that regulates cell–cell adhesion mediated by L1 blocked the enhanced tumorigenic properties conferred by L1. The mechanism of biglycan induction by L1 involves the L1‐NF‐κB pathway. Blocking NF‐κB signaling in L1 expressing cells suppressed the induction of biglycan and the tumorigenic properties conferred by L1. Biglycan expression was undetectable in the normal colonic mucosa, but expressed at highly increased levels in the tumor tissue, especially in the stroma. The therapeutic strategies to target biglycan expression might provide a useful approach for CRC treatment in L1‐overexpressing tumors.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Biglycan; Colorectal cancer (CRC); L1CAM (L1); NF‐κB

An Increase in Mucin2 Expression Is Required for Colon Cancer Progression Mediated by L1 - Saha, Arka; Gavert, Nancy; Brabletz, Thomas; Ben-Ze’ev, Avri (International Journal of Molecular Sciences, 2023)
An induction in the expression of the cell adhesion receptor L1, a Wnt target gene, is a characteristic feature of Wnt/β-catenin activation in colon cancer cells at later stages of the disease. We investigated the proteins secreted following L1 expression in colon cancer cells and identified Mucin2 among the most abundant secreted proteins. We found that suppressing Mucin2 expression in L1-expressing colon cancer cells inhibits cell proliferation, motility, tumorigenesis, and liver metastasis. We detected several signaling pathways involved in Mucin2 induction in L1-expressing cells. In human colon cancer tissue, Mucin2 expression was significantly reduced or lost in the adenocarcinoma tissue, while in the mucinous subtype of colon cancer tissue, Mucin2 expression was increased. An increased signature of L1/Mucin2 expression reduced the survival rate of human colon cancer patients. Thus, induction of Mucin2 expression by L1 is required during mucinous colon cancer progression and can serve as a marker for diagnosis and a target for therapy.
CRIS-Team Scopus Importer:2023-09-15
Keywords: colon cancer; L1; metastasis; Mucin2; tumorigenesis

A novel ZEB1/HAS2 positive feedback loop promotes EMT in breast cancer - Preca, Bogdan-Tiberius; Bajdak, Karolina; Mock, Kerstin; Lehmann, Waltraut; Sundararajan, Vignesh; Bronsert, Peter; Matzge-Ogi, Alexandra; Orian-Rousseau, Veronique; Brabletz, Simone; Brabletz, Thomas; Maurer, Jochen; Stemmler, Marc (Oncotarget, 2017)
Cancer metastasis is the main reason for poor patient survival. Tumor cells delaminate from the primary tumor by induction of epithelial-mesenchymal transition (EMT). EMT is mediated by key transcription factors, including ZEB1, activated by tumor cell interactions with stromal cells and the extracellular matrix (ECM). ZEB1-mediated EMT and motility is accompanied by substantial cell reprogramming and the acquisition of a stemness phenotype. However, understanding of the underlying mechanism is still incomplete. We identified hyaluronic acid (HA), one major ECM proteoglycan and enriched in mammary tumors, to support EMT and enhance ZEB1 expression in cooperation with CD44s. In breast cancer cell lines HA is synthesized mainly by HAS2, which was already shown to be implicated in cancer progression. ZEB1 and HAS2 expression strongly correlates in various cancer entities and high HAS2 levels associate with an early relapse. We identified HAS2, tumor cell-derived HA and ZEB1 to form a positive feedback loop as ZEB1, elevated by HA, directly activates HAS2 expression. In an in vitro differentiation model HA-conditioned medium of breast cancer cells is enhancing osteoclast formation, an indicator of tumor cell-induced osteolysis that facilitates formation of bone metastasis. In combination with the previously identified ZEB1/ESRP1/CD44s feedback loop, we found a novel autocrine mechanism how ZEB1 is accelerating EMT.
EVALuna2:10225

An Ovol2-Zeb1 transcriptional circuit regulates epithelial directional migration and proliferation - Haensel, Daniel; Sun, Peng; Maclean, Adam L.; Ma, Xianghui; Zhou, Yuan; Stemmler, Marc; Brabletz, Simone; Berx, Geert; Plikus, Maksim V.; Nie, Qing; Brabletz, Thomas; Dai, Xing (EMBO Reports, 2019)
Directional migration is inherently important for epithelial tissue regeneration and repair, but how it is precisely controlled and coordinated with cell proliferation is unclear. Here, we report that Ovol2, a transcriptional repressor that inhibits epithelial-to-mesenchymal transition (EMT), plays a crucial role in adult skin epithelial regeneration and repair. Ovol2-deficient mice show compromised wound healing characterized by aberrant epidermal cell migration and proliferation, as well as delayed anagen progression characterized by defects in hair follicle matrix cell proliferation and subsequent differentiation. Epidermal keratinocytes and bulge hair follicle stem cells (Bu-HFSCs) lacking Ovol2 fail to expand in culture and display molecular alterations consistent with enhanced EMT and reduced proliferation. Live imaging of wound explants and Bu-HFSCs reveals increased migration speed but reduced directionality, and post-mitotic cell cycle arrest. Remarkably, simultaneous deletion of Zeb1 encoding an EMT-promoting factor restores directional migration to Ovol2-deficient Bu-HFSCs. Taken together, our findings highlight the important function of an Ovol2-Zeb1 EMT-regulatory circuit in controlling the directional migration of epithelial stem and progenitor cells to facilitate adult skin epithelial regeneration and repair.
CRIS-Team WoS Importer:2019-03-06

A p21-ZEB1 complex inhibits epithelial-mesenchymal transition through the microRNA 183-96-182 cluster - Li, Xiao Ling; Hara, Toshifumi; Choi, Youngeun; Subramanian, Murugan; Francis, Princy; Bilke, Sven; Walker, Robert L.; Pineda, Marbin; Zhu, Yuelin; Yang, Yuan; Luo, Ji; Wakefield, Lalage M.; et al. (Molecular and Cellular Biology, 2014)
The tumor suppressor p21 acts as a cell cycle inhibitor and has also been shown to regulate gene expression by functioning as a transcription corepressor. Here, we identified p21-regulated microRNAs (miRNAs) by sequencing small RNAs from isogenic p21(+/+) and p21(-/-) cells. Three abundant miRNA clusters, miR-200b-200a-429, miR-200c-141, and miR-183-96-182, were downregulated in p21-deficient cells. Consistent with the known function of the miR-200 family and p21 in inhibition of the epithelial-mesenchymal transition (EMT), we observed EMT upon loss of p21 in multiple model systems. To explore a role of the miR-183-96-182 cluster in EMT, we identified its genome-wide targets and found that miR-183 and miR-96 repressed common targets, including SLUG, ZEB1, ITGB1, and KLF4. Reintroduction of miR-200, miR-183, or miR-96 in p21(-/-) cells inhibited EMT, cell migration, and invasion. Conversely, antagonizing miR-200 and miR-183-96-182 cluster miRNAs in p21(+/+) cells increased invasion and elevated the levels of VIM, ZEB1, and SLUG mRNAs. Furthermore, we found that p21 forms a complex with ZEB1 at the miR-183-96-182 cluster promoter to inhibit transcriptional repression of this cluster by ZEB1, suggesting a reciprocal feedback loop.
EVALuna2:10193

A point mutation in the extracellular domain of L1 blocks its capacity to confer metastasis in colon cancer cells via CD10 - Haase, G.; Gavert, N.; Brabletz, Thomas; Ben-Ze'Ev, A. (Oncogene, 2017)
The neural L1 transmembrane cell adhesion receptor of the immunoglobulin-like family is a target gene of Wnt-?-catenin signaling in human colorectal cancer (CRC) cells and is expressed at the invasive edge of the tumor tissue. L1 overexpression in cultured CRC cells confers enhanced proliferation, motility and liver metastasis. We have analyzed the mechanisms of L1-mediated signaling in CRC cells by using various point mutations in the L1 ectodomain that are known to cause severe genetically inherited mental retardation disorders in patients. We found that all such L1 ectodomain mutations abolish the ability of L1 to confer metastatic properties in CRC cells. Using gene array analysis, we identified L1-mutation-specific gene expression signatures for the L1/H210Q and L1/D598N mutations. We identified CD10, a metalloprotease (neprilysin, neutral endopeptidase) and a gene that is specifically induced in CRC cells by L1 in an L1/H210Q mutation-specific manner. CD10 expression was required for the L1-mediated induction of cell proliferation, motility and metastasis, as suppression of CD10 levels in L1-expressing CRC cells abolished the L1 effects on CRC progression. The signaling from L1 to CD10 was mediated through the L1-ezrin-NF-?B pathway. In human CRC tissue L1 and CD10 were localized in partially overlapping regions in the more invasive areas of the tumor tissue. The results suggest that CD10 is a necessary component conferring the L1 effects in CRC cells. The identification of gene expression patterns of L1-domain-specific point mutations may provide novel markers and targets for interfering with L1-mediated CRC progression.
EVALuna2:10219

A self-enforcing CD44s/ZEB1 feedback loop maintains EMT and stemness properties in cancer cells - Preca, Bogdan-Tiberius; Bajdak, Karolina; Mock, Kerstin; Sundararajan, Vignesh; Pfannstiel, Jessica; Maurer, Jochen; Wellner, Ulrich; Hopt, Ulrich T.; Brummer, Tilman; Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc P. (International Journal of Cancer, 2015)
Invasion and metastasis of carcinomas are often activated by induction of aberrant epithelial-mesenchymal transition (EMT). This is mainly driven by the transcription factor ZEB1, promoting tumor-initiating capacity correlated with increased expression of the putative stem cell marker CD44. However, the direct link between ZEB1, CD44 and tumourigenesis is still enigmatic. Remarkably, EMT-induced repression of ESRP1 controls alternative splicing of CD44, causing a shift in the expression from the variant CD44v to the standard CD44s isoform. We analyzed whether CD44 and ZEB1 regulate each other and show that ZEB1 controls CD44s splicing by repression of ESRP1 in breast and pancreatic cancer. Intriguingly, CD44s itself activates the expression of ZEB1, resulting in a self-sustaining ZEB1 and CD44s expression. Activation of this novel CD44s-ZEB1 regulatory loop has functional impact on tumor cells, as evident by increased tumor-sphere initiation capacity, drug-resistance and tumor recurrence. In summary, we identified a self-enforcing feedback loop that employs CD44s to activate ZEB1 expression. This renders tumor cell stemness independent of external stimuli, as ZEB1 downregulates ESRP1, further promoting CD44s isoform synthesis.
EVALuna2:10202

A Zeb1/MtCK1 metabolic axis controls osteoclast activation and skeletal remodeling - Zhu, Lingxin; Tang, Yi; Li, Xiao-Yan; Kerk, Samuel A.; Lyssiotis, Costas A.; Feng, Wenqing; Sun, Xiaoyue; Hespe, Geoffrey E.; Wang, Zijun; Stemmler, Marc; Brabletz, Simone; Brabletz, Thomas; et al. (EMBO Journal, 2023)
Osteoclasts are bone-resorbing polykaryons responsible for skeletal remodeling during health and disease. Coincident with their differentiation from myeloid precursors, osteoclasts undergo extensive transcriptional and metabolic reprogramming in order to acquire the cellular machinery necessary to demineralize bone and digest its interwoven extracellular matrix. While attempting to identify new regulatory molecules critical to bone resorption, we discovered that murine and human osteoclast differentiation is accompanied by the expression of Zeb1, a zinc-finger transcriptional repressor whose role in normal development is most frequently linked to the control of epithelial-mesenchymal programs. However, following targeting, we find that Zeb1 serves as an unexpected regulator of osteoclast energy metabolism. In vivo, Zeb1-null osteoclasts assume a hyperactivated state, markedly decreasing bone density due to excessive resorptive activity. Mechanistically, Zeb1 acts in a rheostat-like fashion to modulate murine and human osteoclast activity by transcriptionally repressing an ATP-buffering enzyme, mitochondrial creatine kinase 1 (MtCK1), thereby controlling the phosphocreatine energy shuttle and mitochondrial respiration. Together, these studies identify a novel Zeb1/MtCK1 axis that exerts metabolic control over bone resorption in vitro and in vivo.
CRIS-Team Scopus Importer:2023-03-17
Keywords: bone resorption; mitochondrial creatine kinase; osteoclast; skeletal remodeling; Zeb1

Cancer-associated cells release citrate to support tumour metastatic progression - Drexler, Konstantin; Schmidt, Katharina M.; Jordan, Katrin; Federlin, Marianne; Milenkovic, Vladimir M.; Liebisch, Gerhard; Artati, Anna; Schmidl, Christian; Madej, Gregor; Tokarz, Janina; Cecil, Alexander; Jagla, Wolfgang; et al. (Life Science Alliance, 2021)
Citrate is important for lipid synthesis and epigenetic regulation in addition to ATP production. We have previously reported that cancer cells import extracellular citrate via the pmCiC transporter to support their metabolism. Here, we show for the first time that citrate is supplied to cancer by cancer-associated stroma (CAS) and also that citrate synthesis and release is one of the latter's major metabolic tasks. Citrate release from CAS is controlled by cancer cells through cross-cellular communication. The availability of citrate from CAS regulated the cytokine profile, metabolism and features of cellular invasion. Moreover, citrate released by CAS is involved in inducing cancer progression especially enhancing invasiveness and organ colonisation. In line with the in vitro observations, we show that depriving cancer cells of citrate using gluconate, a specific inhibitor of pmCiC, significantly reduced the growth and metastatic spread of human pancreatic cancer cells in vivo and muted stromal activation and angiogenesis. We conclude that citrate is supplied to tumour cells by CAS and citrate uptake plays a significant role in cancer metastatic progression.
CRIS-Team Scopus Importer:2021-04-09

Cancer cell invasion and EMT marker expression: a three-dimensional study of the human cancer-host interface - Bronsert, P.; Enderle-Ammour, K.; Bader, M.; Timme, S.; Kuehs, M.; Csanadi, A.; Kayser, G.; Kohler, I.; Bausch, D.; Hoeppner, J.; Hopt, U. T.; Keck, T.; et al. (Journal of Pathology, 2014)
Cancer cell invasion takes place at the cancer-host interface and is a prerequisite for distant metastasis. The relationships between current biological and clinical concepts such as cell migration modes, tumour budding and epithelial-mesenchymal transition (EMT) remains unclear in several aspects, especially for the 'real' situation in human cancer. We developed a novel method that provides exact three-dimensional (3D) information on both microscopic morphology and gene expression, over a virtually unlimited spatial range, by reconstruction from serial immunostained tissue slices. Quantitative 3D assessment of tumour budding at the cancer-host interface in human pancreatic, colorectal, lung and breast adenocarcinoma suggests collective cell migration as the mechanism of cancer cell invasion, while single cancer cell migration seems to be virtually absent. Budding tumour cells display a shift towards spindle-like as well as a rounded morphology. This is associated with decreased E-cadherin staining intensity and a shift from membranous to cytoplasmic staining, as well as increased nuclear ZEB1 expression.
EVALuna2:10192

Cytomegalovirus subverts macrophage identity - Baasch, Sebastian; Giansanti, Piero; Kolter, Julia; Riedl, Andre; Forde, Aaron James; Runge, Solveig; Zenke, Simon; Elling, Roland; Halenius, Anne; Brabletz, Simone; Hengel, Hartmut; Kuster, Bernhard; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Cytomegalovirus subverts macrophage identity - Baasch, Sebastian; Giansanti, Piero; Kolter, Julia; Riedl, André; Forde, Aaron James; Runge, Solveig; Zenke, Simon; Elling, Roland; Halenius, Anne; Brabletz, Simone; Hengel, Hartmut; Kuster, Bernhard; et al. (Cell, 2021)
Cytomegaloviruses (CMVs) have co-evolved with their mammalian hosts for millions of years, leading to remarkable host specificity and high infection prevalence. Macrophages, which already populate barrier tissues in the embryo, are the predominant immune cells at potential CMV entry sites. Here we show that, upon CMV infection, macrophages undergo a morphological, immunophenotypic, and metabolic transformation process with features of stemness, altered migration, enhanced invasiveness, and provision of the cell cycle machinery for viral proliferation. This complex process depends on Wnt signaling and the transcription factor ZEB1. In pulmonary infection, mouse CMV primarily targets and reprograms alveolar macrophages, which alters lung physiology and facilitates primary CMV and secondary bacterial infection by attenuating the inflammatory response. Thus, CMV profoundly perturbs macrophage identity beyond established limits of plasticity and rewires specific differentiation processes, allowing viral spread and impairing innate tissue immunity.
CRIS-Team Scopus Importer:2021-07-16
Keywords: alveolar macrophage; CMV; co-evolution; cytomegalovirus; EMT; epithelial-mesenchymal transition; host-pathogen interaction; Legionella pneumophila; macrophage; myeloid cell differentiation; respiratory tract infection

Deregulation of Transcription Factor Networks Driving Cell Plasticity and Metastasis in Pancreatic Cancer - van Roey, Ruthger; Brabletz, Thomas; Stemmler, Marc; Armstark, Isabell (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic cancer is a very aggressive disease with 5-year survival rates of less than 10%. The constantly increasing incidence and stagnant patient outcomes despite changes in treatment regimens emphasize the requirement of a better understanding of the disease mechanisms. Challenges in treating pancreatic cancer include diagnosis at already progressed disease states due to the lack of early detection methods, rapid acquisition of therapy resistance, and high metastatic competence. Pancreatic ductal adenocarcinoma, the most prevalent type of pancreatic cancer, frequently shows dominant-active mutations in KRAS and TP53 as well as inactivation of genes involved in differentiation and cell-cycle regulation (e.g. SMAD4 and CDKN2A). Besides somatic mutations, deregulated transcription factor activities strongly contribute to disease progression. Specifically, transcriptional regulatory networks essential for proper lineage specification and differentiation during pancreas development are reactivated or become deregulated in the context of cancer and exacerbate progression towards an aggressive phenotype. This review summarizes the recent literature on transcription factor networks and epigenetic gene regulation that play a crucial role during tumorigenesis.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ADM—acinar to ductal metaplasia; cellular plasticity; development; epigenetics (chromatin remodelling); PanIN—pancreatic intraepithelial neoplasia; PDAC—pancreatic ductal adenocarcinoma; transcription factors (TFs)

Downregulation of the Tumor Suppressor TFF1 Is Required during Induction of Colon Cancer Progression by L1 - Saha, Arka; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Cancers, 2022)
The immunoglobulin family cell adhesion receptor L1 is induced in CRC cells at the invasive front of the tumor tissue, and confers enhanced proliferation, motility, tumorigenesis, and liver metastasis. To identify putative tumor suppressors whose expression is downregulated in L1-expressing CRC cells, we blocked the L1–ezrin–NF-κB signaling pathway and searched for genes induced under these conditions. We found that TFF1, a protein involved in protecting the mucus epithelial layer of the colon, is downregulated in L1-expressing cells and displays characteristics of a tumor suppressor. Overexpression of TFF1 in L1-transfected human CRC cells blocks the pro-tumorigenic and metastatic properties conferred by L1 by suppressing NF-κB signaling. Immunohistochemical analyses revealed that human CRC tissue samples often lose the expression of TFF1, while the normal mucosa displays TFF1 in goblet cells. Identifying TFF1 as a tumor suppressor in CRC cells could provide a novel marker for L1-mediated CRC development and a potential target for therapy.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cancer cell adhesion and invasion; colon cancer; L1; metastasis; TFF1

Dynamic EMT: a multi-tool for tumor progression - Brabletz, Simone; Schuhwerk, Harald; Brabletz, Thomas; Stemmler, Marc (EMBO Journal, 2021)
The process of epithelial–mesenchymal transition (EMT) is fundamental for embryonic morphogenesis. Cells undergoing it lose epithelial characteristics and integrity, acquire mesenchymal features, and become motile. In cancer, this program is hijacked to confer essential changes in morphology and motility that fuel invasion. In addition, EMT is increasingly understood to orchestrate a large variety of complementary cancer features, such as tumor cell stemness, tumorigenicity, resistance to therapy and adaptation to changes in the microenvironment. In this review, we summarize recent findings related to these various classical and non-classical functions, and introduce EMT as a true tumorigenic multi-tool, involved in many aspects of cancer. We suggest that therapeutic targeting of the EMT process will—if acknowledging these complexities—be a possibility to concurrently interfere with tumor progression on many levels.
CRIS-Team Scopus Importer:2021-09-10
Keywords: cancer; cell plasticity; EMT; hybrid EMT; invasion; MET; metastasis; partial EMT; signaling pathways; SLUG; SNAIL; tumor stemness; TWIST; ZEB1; ZEB2

EMT in cancer - Brabletz, Thomas; Kalluri, Raghu; Nieto, M. Angela; Weinberg, Robert A. (Nature Reviews Cancer, 2018)
Similar to embryonic development, changes in cell phenotypes defined as an epithelial to mesenchymal transition (EMT) have been shown to play a role in the tumorigenic process. Although the first description of EMT in cancer was in cell cultures, evidence for its role in vivo is now widely reported but also actively debated. Moreover, current research has exemplified just how complex this phenomenon is in cancer, leaving many exciting, open questions for researchers to answer in the future. With these points in mind, we asked four scientists for their opinions on the role of EMT in cancer and the challenges faced by scientists working in this fast-moving field.
EVALuna2:10236

EMT transcription factor ZEB1 alters the epigenetic landscape of colorectal cancer cells - Lindner, Pablo; Paul, Sushmita; Eckstein, Markus; Hampel, Chuanpit; Muenzner, Julienne K.; Erlenbach-Wuensch, Katharina; Ahmed, Husayn P.; Mahadevan, Vijayalakshmi; Brabletz, Thomas; Hartmann, Arndt; Vera, Julio; Schneider-Stock, Regine (Cell Death & Disease, 2020)
Epigenetic deregulation remarkably triggers mechanisms associated with tumor aggressiveness like epithelial–mesenchymal transition (EMT). Since EMT is a highly complex, but also reversible event, epigenetic processes such as DNA methylation or chromatin alterations must be involved in its regulation. It was recently described that loss of the cell cycle regulator p21 was associated with a gain in EMT characteristics and an upregulation of the master EMT transcription factor ZEB1. In this study, in silico analysis was performed in combination with different in vitro and in vivo techniques to identify and verify novel epigenetic targets of ZEB1, and to proof the direct transcriptional regulation of SETD1B by ZEB1. The chorioallantoic-membrane assay served as an in vivo model to analyze the ZEB1/SETD1B interaction. Bioinformatical analysis of CRC patient data was used to examine the ZEB1/SETD1B network under clinical conditions and the ZEB1/SETD1B network was modeled under physiological and pathological conditions. Thus, we identified a self-reinforcing loop for ZEB1 expression and found that the SETD1B associated active chromatin mark H3K4me3 was enriched at the ZEB1 promoter in EMT cells. Moreover, clinical evaluation of CRC patient data showed that the simultaneous high expression of ZEB1 and SETD1B was correlated with the worst prognosis. Here we report that the expression of chromatin modifiers is remarkably dysregulated in EMT cells. SETD1B was identified as a new ZEB1 target in vitro and in vivo. Our study demonstrates a novel example of an activator role of ZEB1 for the epigenetic landscape in colorectal tumor cells.
CRIS-Team Scopus Importer:2020-03-20

Enhancer cooperativity as a novel mechanism underlying the transcriptional regulation of E-cadherin during mesenchymal to epithelial transition - Alotaibi, Hani; Basilicata, M. Felicia; Shehwana, Huma; Kosowan, Tyler; Schreck, Ilona; Braeutigam, Christien; Konu, Ozlen; Brabletz, Thomas; Stemmler, Marc (BBA - Biochimica et Biophysica Acta, 2015)
Epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) highlight crucial steps during embryogenesis and tumorigenesis. Induction of dramatic changes in gene expression and cell features is reflected by modulation of Cdh1 (E-cadherin) expression. We show that Cdh1 activity during MET is governed by two enhancers at +7.8kb and at +11.5kb within intron 2 that are activated by binding of Grhl3 and Hnf4?, respectively. Recruitment of Grhl3 and Hnf4? to the enhancers is crucial for activating Cdh1 and accomplishing MET in non-tumorigenic mouse mammary gland cells (NMuMG). Moreover, the two enhancers cooperate via Grhl3 and Hnf4? binding, induction of DNA-looping and clustering at the promoter to orchestrate E-cadherin re-expression. Our results provide novel insights into the cellular mechanisms whereby cells respond to MET signals and re-establish an epithelial phenotype by enhancer cooperativity. A general importance of our findings including MET-mediated colonization of metastasizing tumor cells is suggested.
EVALuna2:10189

Epithelial-mesenchymal transition induces endoplasmic-reticulum-stress response in human colorectal tumor cells - Zeindl-Eberhart, Evelyn; Brandl, Lydia; Liebmann, Sibylle; Ormanns, Steffen; Scheel, Silvio K.; Brabletz, Thomas; Kirchner, Thomas; Jung, Andreas (PLoS ONE, 2014)
Tumor cells are stressed by unfavorable environmental conditions like hypoxia or starvation. Driven by the resulting cellular stress tumor cells undergo epithelial-mesenchymal transition. Additionally, cellular stress is accompanied by endoplasmic reticulum-stress which induces an unfolded protein response. It is unknown if epithelial-mesenchymal transition and endoplasmic reticulum-stress are occurring as independent parallel events or if an interrelationship exists between both of them. Here, we show that in colorectal cancer cells endoplasmic reticulum-stress depends on the induction of ZEB-1, which is a main factor of epithelial-mesenchymal transition. In the absence of ZEB-1 colorectal cancer cells cannot mount endoplasmic reticulum-stress as a reaction on cellular stress situations like hypoxia or starvation. Thus, our data suggest that there is a hierarchy in the development of cellular stress which starts with the presence of environmental stress that induces epithelial-mesenchymal transition which allows finally endoplasmic reticulum-stress. This finding highlights the central role of epithelial-mesenchymal transition during the process of tumorigenesis as epithelial-mesenchymal transition is also associated with chemoresistance and cancer stemness. Consequently, endoplasmic reticulum-stress might be a well suited target for chemotherapy of colorectal cancers.
EVALuna2:10196

ERN1 and ALPK1 inhibit differentiation of bi-potential tumor-initiating cells in human breast cancer - Strietz, Juliane; Stepputtis, Stella S.; Preca, Bogdan-Tiberius; Vannier, Corinne; Kim, Mihee M.; Castro, David J.; Au, Qingyan; Boerries, Melanie; Busch, Hauke; Aza-Blanc, Pedro; Heynen-Genel, Susanne; Bronsert, Peter; et al. (Oncotarget, 2016)
Cancers are heterogeneous by nature. While traditional oncology screens commonly use a single endpoint of cell viability, altering the phenotype of tumor-initiating cells may reveal alternative targets that regulate cellular growth by processes other than apoptosis or cell division. We evaluated the impact of knocking down expression of 420 kinases in bi-lineage triple-negative breast cancer (TNBC) cells that express characteristics of both myoepithelial and luminal cells. Knockdown of ERN1 or ALPK1 induces bi-lineage MDA-MB-468 cells to lose the myoepithelial marker keratin 5 but not the luminal markers keratin 8 and GATA3. In addition, these cells exhibit increased ?-casein production. These changes are associated with decreased proliferation and clonogenicity in spheroid cultures and anchorage-independent growth assays. Confirmation of these assays was completed in vivo, where ERN1- or ALPK1-deficient TNBC cells are less tumorigenic. Finally, treatment with K252a, a kinase inhibitor active on ERN1, similarly impairs anchorage-independent growth of multiple breast cancer cell lines. This study supports the strategy to identify new molecular targets for types of cancer driven by cells that retain some capacity for normal differentiation to a non-tumorigenic phenotype. ERN1 and ALPK1 are potential targets for therapeutic development.
EVALuna2:10224

Form follows function: Morphological and immunohistological insights into epithelial-mesenchymal transition characteristics of tumor buds - Enderle-Ammour, Kathrin; Bader, Moritz; Ahrens, Theresa Dorothee; Franke, Kai; Timme, Sylvia; Csanadi, Agnes; Hoeppner, Jens; Kulemann, Birte; Maurer, Jochen; Reiss, Philip; Schilling, Oliver; Keck, Tobias; et al. (Tumor Biology, 2017)
In cancer biology, the architectural concept "form follows function" is reflected by cell morphology, migration, and epithelial-mesenchymal transition protein pattern. In vivo, features of epithelial-mesenchymal transition have been associated with tumor budding, which correlates significantly with patient outcome. Hereby, the majority of tumor buds are not truly detached but still connected to a major tumor mass. For detailed insights into the different tumor bud types and the process of tumor budding, we quantified tumor cells according to histomorphological and immunohistological epithelial-mesenchymal transition characteristics. Three-dimensional reconstruction from adenocarcinomas (pancreatic, colorectal, lung, and ductal breast cancers) was performed as published. Tumor cell morphology and epithelial-mesenchymal transition characteristics (represented by zinc finger E-box-binding homeobox 1 and E-Cadherin) were analyzed qualitatively and quantitatively in a three-dimensional context. Tumor buds were classified into main tumor mass, connected tumor bud, and isolated tumor bud. Cell morphology and epithelial-mesenchymal transition marker expression were assessed for each tumor cell. Epithelial-mesenchymal transition characteristics between isolated tumor bud and connected tumor bud demonstrated no significant differences or trends. Tumor cell count correlated significantly with epithelial-mesenchymal transition and histomorphological characteristics. Regression curve analysis revealed initially a loss of membranous E-Cadherin, followed by expression of cytoplasmic E-Cadherin and subsequent expression of nuclear zinc finger E-box-binding homeobox 1. Morphologic changes followed later in this sequence. Our data demonstrate that connected and isolated tumor buds are equal concerning immunohistochemical epithelial-mesenchymal transition characteristics and histomorphology. Our data also give an insight in the process of tumor budding. While there is a notion that the epithelial-mesenchymal transition zinc finger E-box-binding homeobox 1-E-Cadherin cascade is initiated by zinc finger E-box-binding homeobox 1, our results are contrary and outline other possible pathways influencing the regulation of E-Cadherin.
EVALuna2:10228

Generation and characterization of mice for conditional inactivation of Zeb1 - Brabletz, Simone; Lasierra Losada, Maria; Schmalhofer, Otto; Mitschke, Julia; Krebs, Angela; Brabletz, Thomas; Stemmler, Marc (Genesis, 2017)
The multizinc finger containing transcription factor ZEB1 plays crucial roles during various aspects of mammalian development and tumorigenesis. Best studied in human tumors, ZEB1 is activating the embryo-derived program of epithelial-mesenchymal transition (EMT). The aberrant activation of EMT confers an invasive metastasizing phenotype with acquisition of stem cell properties and resistance to radio- and chemotherapy. Although ZEB1 has very important functions in tumor progression, not much is known about its role in physiological contexts and during development and homeostasis. We describe the generation of Zeb1(flox/flox) mice carrying a targeted mutation for conditional Zeb1 gene inactivation and show that homozygous Zeb1-depletion in the germline results in a phenotype similar to the conventional Zeb1 knockout.
EVALuna:33906

Genome-wide cooperation of EMT transcription factor ZEB1 with YAP and AP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Bönisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and the EMT-inducing transcription factor ZEB1 is a crucial stimulator of these processes. While work on ZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wide ZEB1 binding study in triple-negative breast cancer cells. We identified ZEB1 as a novel interactor of the AP-1 factors FOSL1 and JUN and show that, together with the Hippo pathway effector YAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression of ZEB1, YAP, FOSL1 and JUN marks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors: ZEB1, AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team Scopus Importer:2020-07-31
Keywords: AP-1; breast cancer; epithelial to mesenchymal transition; ZEB1

Genome-wide cooperation ofEMTtranscription factorZEB1 withYAPandAP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Boenisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and theEMT-inducing transcription factorZEB1 is a crucial stimulator of these processes. While work onZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wideZEB1 binding study in triple-negative breast cancer cells. We identifiedZEB1 as a novel interactor of theAP-1 factorsFOSL1 andJUNand show that, together with the Hippo pathway effectorYAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression ofZEB1,YAP,FOSL1 andJUNmarks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors:ZEB1,AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team WoS Importer:2020-09-25

Gpr126 (Adgrg6) is expressed in cell types known to be exposed to mechanical stimuli - Musa, Gentian; Cazorla-Vázquez, Salvador; van Amerongen, Machteld J.; Stemmler, Marc; Eckstein, Markus; Hartmann, Arndt; Braun, Thomas; Brabletz, Thomas; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
GPR126 (ADGRG6) is an adhesion G protein–coupled receptor that plays an important role in a variety of tissues/organs, such as heart, sciatic nerve, cartilage, and ear. Moreover, GPR126 (ADGRG6) mutations are associated with human diseases, like adolescent idiopathic scoliosis, lung disease, bladder cancer, and intellectual disability. Despite its clinical importance, it remains elusive how GPR126 is activated and mediates signal transduction and what cellular processes depend on GPR126 signaling. Here, we generated a lacZ reporter mouse line to determine endogenous Gpr126 (Adgrg6) expression in a cell type-specific manner during embryonic development, at postnatal day 5 and in adult animals. Our results confirm Gpr126 expression data previously obtained utilizing antibodies and in situ hybridization in embryonic heart and sciatic nerve. In addition, we provide data with cellular resolution for previously described RT-PCR–based data, including lung and bladder. Moreover, new Gpr126-expressing tissues and cell types were identified, such as ureter and acinar secretory cells. Collectively, our data demonstrate that the newly generated lacZ reporter mouse is a suitable model to study Gpr126 expression during development and adulthood, provide detailed insight into Gpr126 expression at the cellular level, and reveal that all identified Gpr126-expressing cells are known to be exposed to mechanical stimuli.
CRIS-Team Scopus Importer:2019-06-28
Keywords: ADGRG6; chondrocytes; endothelium; epithelium

Guidelines and definitions for research on epithelial–mesenchymal transition - Yang, Jing; Antin, Parker; Berx, Geert; Blanpain, Cédric; Brabletz, Thomas; Bronner, Marianne; Campbell, Kyra; Cano, Amparo; Casanova, Jordi; Christofori, Gerhard; Dedhar, Shoukat; Derynck, Rik; et al. (Nature Reviews Molecular Cell Biology, 2020)
Epithelial–mesenchymal transition (EMT) encompasses dynamic changes in cellular organization from epithelial to mesenchymal phenotypes, which leads to functional changes in cell migration and invasion. EMT occurs in a diverse range of physiological and pathological conditions and is driven by a conserved set of inducing signals, transcriptional regulators and downstream effectors. With over 5,700 publications indexed by Web of Science in 2019 alone, research on EMT is expanding rapidly. This growing interest warrants the need for a consensus among researchers when referring to and undertaking research on EMT. This Consensus Statement, mediated by ‘the EMT International Association’ (TEMTIA), is the outcome of a 2-year-long discussion among EMT researchers and aims to both clarify the nomenclature and provide definitions and guidelines for EMT research in future publications. We trust that these guidelines will help to reduce misunderstanding and misinterpretation of research data generated in various experimental models and to promote cross-disciplinary collaboration to identify and address key open questions in this research field. While recognizing the importance of maintaining diversity in experimental approaches and conceptual frameworks, we emphasize that lasting contributions of EMT research to increasing our understanding of developmental processes and combatting cancer and other diseases depend on the adoption of a unified terminology to describe EMT.
CRIS-Team Scopus Importer:2020-05-02

Inactivation of Zeb1 in GRHL2-deficient mouse embryos rescues mid-gestation viability and secondary palate closure - Carpinelli, Marina R.; De Vries, Michael E.; Auden, Alana; Butt, Tariq; Deng, Zihao; Partridge, Darren D.; Miles, Lee B.; Georgy, Smitha R.; Haigh, Jody J.; Darido, Charbel; Brabletz, Simone; Brabletz, Thomas; et al. (Disease Models & Mechanisms, 2020)
Cleft lip and palate are common birth defects resulting from failure of the facial processes to fuse during development. The mammalian grainyhead-like (Grhl1-3) genes play key roles in a number of tissue fusion processes including neurulation, epidermal wound healing and eyelid fusion. One family member, Grhl2, is expressed in the epithelial lining of the first pharyngeal arch in mice at embryonic day (E)10.5, prompting analysis of the role of this factor in palatogenesis. Grhl2- null mice die at E11.5 with neural tube defects and a cleft face phenotype, precluding analysis of palatal fusion at a later stage of development. However, in the first pharyngeal arch of Grhl2-null embryos, dysregulation of transcription factors that drive epithelialmesenchymal transition (EMT) occurs. The aberrant expression of these genes is associated with a shift in RNA-splicing patterns that favours the generation of mesenchymal isoforms of numerous regulators. Driving the EMT perturbation is loss of expression of the EMT-suppressing transcription factors Ovol1 and Ovol2, which are direct GRHL2 targets. The expression of the miR-200 family of microRNAs, also GRHL2 targets, is similarly reduced, resulting in a 56-fold upregulation of Zeb1 expression, a major driver of mesenchymal cellular identity. The critical role of GRHL2 in mediating cleft palate in Zeb1-/- mice is evident, with rescue of both palatal and facial fusion seen in Grhl2-/-;Zeb1-/- embryos. These findings highlight the delicate balance between GRHL2/ZEB1 and epithelial/mesenchymal cellular identity that is essential for normal closure of the palate and face. Perturbation of this pathway may underlie cleft palate in some patients.
CRIS-Team Scopus Importer:2020-04-14
Keywords: EMT; Explant; Grhl2; Palate; Zeb1

Inappropriate cadherin switching in the mouse epiblast compromises proper signaling between the epiblast and the extraembryonic ectoderm during gastrulation - Basilicata, M. Felicia; Frank, Marcus; Solter, Davor; Brabletz, Thomas; Stemmler, Marc (Scientific Reports, 2016)
Cadherin switching from E-cadherin (E-cad) to N-cadherin (N-cad) is a key step of the epithelial-mesenchymal transition (EMT) processes that occurs during gastrulation and cancer progression. We investigate whether cadherins actively participate in progression of EMT by crosstalk to signaling pathways. We apply ectopic cadherin switching before the onset of mouse gastrulation. Mutants with an induced E-cad to N-cad switch (Ncadki) die around E8.5. Severe morphological changes including a small epiblast, a rounded shape, an enlarged extra-embryonic compartment and lack of the amnion, combined with a massive cell detachment from the ectodermal layer are detected. In contrast to epiblast-specific E-cad depletion, gastrulation is initiated in Ncadki embryos, but patterning of the germ-layers is abnormal. An overall reduction in BMP signaling, expansion of Nodal and Eomes domains, combined with reduced Wnt3a expression at the primitive streak is observed. Our results show that in addition to cadherin-dependent adhesion, proper embryonic development requires E-cad mediated signaling function to facilitate a feedback loop that stabilizes Bmp4 and Bmp2 expression in the extraembryonic ectoderm and sustained downstream activity in the epiblast. Moreover, for proper morphogenesis a fine-tuned spatio-temporal control of cadherin switching is required during EMT at gastrulation to avoid premature cell detachment and migration.
EVALuna2:10216

Increased expression of cathepsin D is required for L1-mediated colon cancer progression. - Basu, Sayon; Cheriyamundath, Sanith; Gavert, Nancy; Brabletz, Thomas; Haase, Gal; Ben-Ze'Ev, Avri (Oncotarget, 2019)
Hyperactivation of Wnt/β-catenin target genes is considered a key step in human colorectal cancer (CRC) development. We previously identified the immunoglobulin-like cell adhesion receptor L1 as a target gene of β-catenin/TCF transactivation that is localized at the invasive edge of CRC tissue. Using gene arrays, we discovered a number of downstream target genes and signaling pathways conferred by L1 overexpression during colon cancer progression. Here, we have used a proteomic approach to identify proteins in the secretome of L1-overexpressing CRC cells and studied the role of the increase in the aspartate protease cathepsin D (CTSD) in L1-mediated colon cancer development. We found that in addition to the increase in CTSD in the secretome, the RNA and protein levels of CTSD were also induced by L1 in CRC cells. CTSD overexpression resulted in elevated proliferation under stress and increased motility, tumorigenesis and liver metastasis, although to a lesser extent than after L1-transfection. The suppression of endogenous CTSD in L1-expressing cells blocked the increase in the proliferative, motile, tumorigenic and metastatic ability of CRC cells. Enhancing Wnt/β-catenin signaling by the inhibition of GSK3β resulted in increased endogenous CTSD levels, suggesting the involvement of the Wnt/β-catenin pathway in CTSD expression. In human CRC tissue, CTSD was detected in epithelial cells and in the stromal compartment at the more invasive areas of the tumor, but not in the normal mucosa, indicating that CTSD plays an essential role in CRC progression.
EVALuna2:203933

Increased expression of cathepsin D is required for L1-mediated colon cancer progression - Basu, Sayon; Cheriyamundath, Sanith; Gavert, Nancy; Brabletz, Thomas; Haase, Gal; Ben-Ze'Ev, Avri (Oncotarget, 2019)
Hyperactivation of Wnt/β-catenin target genes is considered a key step in human colorectal cancer (CRC) development. We previously identified the immunoglobulin-like cell adhesion receptor L1 as a target gene of β-catenin/TCF transactivation that is localized at the invasive edge of CRC tissue. Using gene arrays, we discovered a number of downstream target genes and signaling pathways conferred by L1 overexpression during colon cancer progression. Here, we have used a proteomic approach to identify proteins in the secretome of L1-overexpressing CRC cells and studied the role of the increase in the aspartate protease cathepsin D (CTSD) in L1-mediated colon cancer development. We found that in addition to the increase in CTSD in the secretome, the RNA and protein levels of CTSD were also induced by L1 in CRC cells. CTSD overexpression resulted in elevated proliferation under stress and increased motility, tumorigenesis and liver metastasis, although to a lesser extent than after L1-transfection. The suppression of endogenous CTSD in L1-expressing cells blocked the increase in the proliferative, motile, tumorigenic and metastatic ability of CRC cells. Enhancing Wnt/β-catenin signaling by the inhibition of GSK3β resulted in increased endogenous CTSD levels, suggesting the involvement of the Wnt/β-catenin pathway in CTSD expression. In human CRC tissue, CTSD was detected in epithelial cells and in the stromal compartment at the more invasive areas of the tumor, but not in the normal mucosa, indicating that CTSD plays an essential role in CRC progression.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Cathepsin D; Colon cancer; L1; Metastasis; Wnt/β-catenin signaling

Inducible mouse models of colon cancer for the analysis of sporadic and inflammation-driven tumor progression and lymph node metastasis - Neufert, Clemens; Heichler, Christina; Brabletz, Thomas; Scheibe, Kristina; Boonsanay, Verawan; Greten, Florian R.; Neurath, Markus (Nature Protocols, 2020)
Despite advances in the detection and therapy of colorectal cancer (CRC) in recent years, CRC has remained a major challenge in clinical practice. Although alternative methods for modeling CRC have been developed, animal models of CRC remain helpful when analyzing molecular aspects of pathogenesis and are often used to perform preclinical in vivo studies of potential therapeutics. This protocol updates our protocol published in 2007, which provided an azoxymethane (AOM)-based setup for investigations into sporadic (Step 5A) and, when combined with dextran sodium sulfate (Step 5B), inflammation-associated tumor growth. This update also extends the applications beyond those of the original protocol by including an option in which AOM is serially applied to mice with p53 deficiency in the intestinal epithelium (Step 5C). In this model, the combination of p53 deficiency and AOM promotes tumor development, including growth of invasive cancers and lymph node metastasis. It also provides details on analysis of colorectal tumor growth and metastasis, including analysis of partial epithelial-to-mesenchymal transition, cell isolation and co-culture studies, high-resolution mini-endoscopy, light-sheet fluorescence microscopy and micro-CT imaging in mice. The target audience for our protocol is researchers who plan in vivo studies to address mechanisms influencing sporadic or inflammation-driven tumor development, including the analysis of local invasiveness and lymph node metastasis. It is suitable for preclinical in vivo testing of novel drugs and other interventional strategies for clinical translation, plus the evaluation of emerging imaging devices/modalities. It can be completed within 24 weeks (using Step 5A/C) or 10 weeks (using Step 5B).
CRIS-Team WoS Importer:2021-01-01

Induction of the intestinal stem cell signature gene SMOC-2 is required for L1-mediated colon cancer progression - Shvab, A.; Haase, G.; Ben-Shmuel, A.; Gavert, N.; Brabletz, Thomas; Dedhar, S.; Ben-Ze'Ev, A. (Oncogene, 2016)
Overactivation of Wnt-?-catenin signaling, including ?-catenin-TCF target gene expression, is a hallmark of colorectal cancer (CRC) development. We identified the immunoglobulin family of cell-adhesion receptors member L1 as a ?-catenin-TCF target gene preferentially expressed at the invasive edge of human CRC tissue. L1 can confer enhanced motility and liver metastasis when expressed in CRC cells. This ability of L1-mediated metastasis is exerted by a mechanism involving ezrin and the activation of NF-?B target genes. In this study, we identified the secreted modular calcium-binding matricellular protein-2 (SMOC-2) as a gene activated by L1-ezrin-NF-?B signaling. SMOC-2 is also known as an intestinal stem cell signature gene in mice expressing Lgr5 in cells at the bottom of intestinal crypts. The induction of SMOC-2 expression in L1-expressing CRC cells was necessary for the increase in cell motility, proliferation under stress and liver metastasis conferred by L1. SMOC-2 expression induced a more mesenchymal like phenotype in CRC cells, a decrease in E-cadherin and an increase in Snail by signaling that involves integrin-linked kinase (ILK). SMOC-2 was localized at the bottom of normal human colonic crypts and at increased levels in CRC tissue with preferential expression in invasive areas of the tumor. We found an increase in Lgr5 levels in CRC cells overexpressing L1, p65 or SMOC-2, suggesting that L1-mediated CRC progression involves the acquisition of a stem cell-like phenotype, and that SMOC-2 elevation is necessary for L1-mediated induction of more aggressive/invasive CRC properties.
EVALuna2:10198

Interconnected feedback loops among ESRP1, HAS2, and CD44 regulate epithelial-mesenchymal plasticity in cancer - Jolly, Mohit Kumar; Preca, Bogdan-Tiberius; Tripathi, Satyendra C.; Jia, Dongya; George, Jason T.; Hanash, Samir M.; Brabletz, Thomas; Stemmler, Marc; Maurer, Jochen; Levine, Herbert (APL Bioengineering, 2018)
Aberrant activation of epithelial-mesenchymal transition (EMT) in carcinoma cells contributes to increased migration and invasion, metastasis, drug resistance, and tumor-initiating capacity. EMT is not always a binary process; rather, cells may exhibit a hybrid epithelial/mesenchymal (E/M) phenotype. ZEB1-a key transcription factor driving EMT-can both induce and maintain a mesenchymal phenotype. Recent studies have identified two novel autocrine feedback loops utilizing epithelial splicing regulatory protein 1 (ESRP1), hyaluronic acid synthase 2 (HAS2), and CD44 which maintain high levels of ZEB1. However, how the crosstalk between these feedback loops alters the dynamics of epithelial-hybrid-mesenchymal transition remains elusive. Here, using an integrated theoretical-experimental framework, we identify that these feedback loops can enable cells to stably maintain a hybrid E/M phenotype. Moreover, computational analysis identifies the regulation of ESRP1 as a crucial node, a prediction that is validated by experiments showing that knockdown of ESRP1 in stable hybrid E/M H1975 cells drives EMT. Finally, in multiple breast cancer datasets, high levels of ESRP1, ESRP1/HAS2, and ESRP1/ZEB1 correlate with poor prognosis, supporting the relevance of ZEB1/ESRP1 and ZEB1/HAS2 axes in tumor progression. Together, our results unravel how these interconnected feedback loops act in concert to regulate ZEB1 levels and to drive the dynamics of epithelial-hybrid-mesenchymal transition.
EVALuna2:201924

Interplay between the EMT transcription factors ZEB1 and ZEB2 regulates hematopoietic stem and progenitor cell differentiation and hematopoietic lineage fidelity - Wang, Jueqiong; Farkas, Carlos; Benyoucef, Aissa; Carmichael, Catherine; Haigh, Katharina; Wong, Nick; Huylebroeck, Danny; Stemmler, Marc P.; Brabletz, Simone; Brabletz, Thomas; Nefzger, Christian M.; Goossens, Steven; et al. (Plos Biology, 2021)
The ZEB2 transcription factor has been demonstrated to play important roles in hematopoiesis and leukemic transformation. ZEB1 is a close family member of ZEB2 but has remained more enigmatic concerning its roles in hematopoiesis. Here, we show using conditional loss-of-function approaches and bone marrow (BM) reconstitution experiments that ZEB1 plays a cell-autonomous role in hematopoietic lineage differentiation, particularly as a positive regulator of monocyte development in addition to its previously reported important role in T-cell differentiation. Analysis of existing single-cell (sc) RNA sequencing (RNA-seq) data of early hematopoiesis has revealed distinctive expression differences between Zeb1 and Zeb2 in hematopoietic stem and progenitor cell (HSPC) differentiation, with Zeb2 being more highly and broadly expressed than Zeb1 except at a key transition point (short-term HSC [ST-HSC]?MPP1), whereby Zeb1 appears to be the dominantly expressed family member. Inducible genetic inactivation of both Zeb1 and Zeb2 using a tamoxifen-inducible Cre-mediated approach leads to acute BM failure at this transition point with increased long-term and short-term hematopoietic stem cell numbers and an accompanying decrease in all hematopoietic lineage differentiation. Bioinformatics analysis of RNA-seq data has revealed that ZEB2 acts predominantly as a transcriptional repressor involved in restraining mature hematopoietic lineage gene expression programs from being expressed too early in HSPCs. ZEB1 appears to fine-tune this repressive role during hematopoiesis to ensure hematopoietic lineage fidelity. Analysis of Rosa26 locus-based transgenic models has revealed that Zeb1 as well as Zeb2 cDNA-based overexpression within the hematopoietic system can drive extramedullary hematopoiesis/splenomegaly and enhance monocyte development. Finally, inactivation of Zeb2 alone or Zeb1/2 together was found to enhance survival in secondary MLL-AF9 acute myeloid leukemia (AML) models attesting to the oncogenic role of ZEB1/2 in AML.
CRIS-Team WoS Importer:2021-10-01

ISG15 induction is required during L1-mediated colon cancer progression and metastasis. - Cheriyamundath, Sanith; Basu, Sayon; Haase, Gal; Doernberg, Harry; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Oncotarget, 2019)
Hyperactivation of Wnt/β-catenin target gene expression is a hallmark of colorectal cancer (CRC) development. We identified L1-CAM (L1) and Nr-CAM, members of the immunoglobulin family of nerve cell adhesion receptors, as target genes of the Wnt/β-catenin pathway in CRC cells. L1 overexpression in CRC cells enhances their motile and tumorigenic capacity and promotes liver metastasis. L1 is often localized at the invasive edge of CRC tissue. Using gene arrays and proteomic analyses we identified downstream signaling pathways and targets of L1-mediated signaling. Here, we found that the expression of interferon-stimulated gene 15 (ISG15) that operates much like ubiquitin (is conjugated to proteins by ISGylation), is elevated in the conditioned medium and in CRC cells overexpressing L1. Suppression of endogenous ISG15 levels in L1-expressing cells blocked the increased proliferative, motile, tumorigenic and liver metastatic capacities of CRC cells. ISG15 overexpression, on its own, could enhance these properties in CRC cells, but only to a much lower extent compared to L1. We show that NF-κB signaling is involved in the L1-mediated increase in ISG15, since blocking the NF-κB pathway abolished the induction of ISG15 by L1. Point mutations in the L1 ectodomain that interfere with its binding to L1 ligands, also inhibited the increase in ISG15. We detected high levels of ISG15 in human CRC tissue cells and in the adjacent stroma, but not in the normal mucosa. The results suggest that ISG15 is involved in L1-mediated CRC development and is a potential target for CRC therapy.
EVALuna2:384412

ISG15 induction is required during L1-mediated colon cancer progression and metastasis - Cheriyamundath, Sanith; Basu, Sayon; Haase, Gal; Doernberg, Harry; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Oncotarget, 2019)
Hyperactivation of Wnt/β-catenin target gene expression is a hallmark of colorectal cancer (CRC) development. We identified L1-CAM (L1) and Nr-CAM, members of the immunoglobulin family of nerve cell adhesion receptors, as target genes of the Wnt/β-catenin pathway in CRC cells. L1 overexpression in CRC cells enhances their motile and tumorigenic capacity and promotes liver metastasis. L1 is often localized at the invasive edge of CRC tissue. Using gene arrays and proteomic analyses we identified downstream signaling pathways and targets of L1-mediated signaling. Here, we found that the expression of interferon-stimulated gene 15 (ISG15) that operates much like ubiquitin (is conjugated to proteins by ISGylation), is elevated in the conditioned medium and in CRC cells overexpressing L1. Suppression of endogenous ISG15 levels in L1-expressing cells blocked the increased proliferative, motile, tumorigenic and liver metastatic capacities of CRC cells. ISG15 overexpression, on its own, could enhance these properties in CRC cells, but only to a much lower extent compared to L1. We show that NF-κB signaling is involved in the L1-mediated increase in ISG15, since blocking the NF-κB pathway abolished the induction of ISG15 by L1. Point mutations in the L1 ectodomain that interfere with its binding to L1 ligands, also inhibited the increase in ISG15. We detected high levels of ISG15 in human CRC tissue cells and in the adjacent stroma, but not in the normal mucosa. The results suggest that ISG15 is involved in L1-mediated CRC development and is a potential target for CRC therapy.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Colorectal cancer; ISG15; L1; Metastasis

Loss of the transcription factor ZEB1 from cDC1s reveals a crucial role for cDC1s in maintaining cDC2s and Macrophages in the spleen - Soen, B.; Van Gassen, S.; Saeys, Yvan; Brabletz, Thomas; Malissen, B.; Lambrecht, B.; Berx, G.; Scott, C. (2018)
EVALuna2:34672

miR-200c dampens cancer cell migration via regulation of protein kinase A subunits - Sigloch, Florian Christoph; Burk, Ulrike Christina; Biniossek, Martin Lothar; Brabletz, Thomas; Schilling, Oliver (Oncotarget, 2015)
Expression of miR-200c is a molecular switch to determine cellular fate towards a mesenchymal or epithelial phenotype. miR-200c suppresses the early steps of tumor progression by preventing epithelial-mesenchymal transition (EMT) and intravasation of tumor cells. Unraveling the underlying molecular mechanisms might pinpoint to novel therapeutic options. To better understand these mechanisms it is crucial to identify targets of miR-200c. Here, we employ a combination of quantitative proteomic and bioinformatic strategies to identify novel miR-200c targets. We identify and confirm two subunits of the central cellular kinase protein kinase A (PKA), namely PRKAR1A and PRKACB, to be directly regulated by miR-200c. Notably, siRNA-mediated downregulation of both proteins phenocopies the migratory behavior of breast cancer cells after miR-200c overexpression. Patient data from publicly accessible databases supports a miR-200c-PKA axis. Thus, our study identifies the PKA heteroprotein as an important mediator of miR-200c induced repression of migration in breast cancer cells. By bioinformatics, we define a miRNA target cluster consisting of PRKAR1A, PRKAR2B, PRKACB, and COF2, which is targeted by a group of 14 miRNAs.
EVALuna2:10186

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE

MYC-nick promotes cell migration by inducing fascin expression and Cdc42 activation - Anderson, Sarah; Poudel, Kumud Raj; Roh-Johnson, Minna; Brabletz, Thomas; Yu, Ming; Borenstein-Auerbach, Nofit; Grady, William N.; Bai, Jihong; Moens, Cecilia B.; Eisenman, Robert N.; Conacci-Sorrell, Maralice (Proceedings of the National Academy of Sciences of the United States of America, 2016)
MYC-nick is a cytoplasmic, transcriptionally inactive member of the MYC oncoprotein family, generated by a proteolytic cleavage of full-length MYC. MYC-nick promotes migration and survival of cells in response to chemotherapeutic agents or withdrawal of glucose. Here we report that MYC-nick is abundant in colonic and intestinal tumors derived from mouse models with mutations in the Wnt, TGF-?, and PI3K pathways. Moreover, MYC-nick is elevated in colon cancer cells deleted for FBWX7, which encodes the major E3 ligase of full-length MYC frequently mutated in colorectal cancers. MYC-nick promotes the migration of colon cancer cells assayed in 3D cultures or grown as xenografts in a zebrafish metastasis model. MYC-nick accelerates migration by activating the Rho GTPase Cdc42 and inducing fascin expression. MYC-nick, fascin, and Cdc42 are frequently up-regulated in cells present at the invasive front of human colorectal tumors, suggesting a coordinated role for these proteins in tumor migration.
EVALuna2:10218

MYC promotes tryptophan uptake and metabolism by the kynurenine pathway in colon cancer - Venkateswaran, Niranjan; Lafita-Navarro, M. Carmen; Hao, Yi Heng; Kilgore, Jessica A.; Perez-Castro, Lizbeth; Braverman, Jonathan; Borenstein-Auerbach, Nofit; Kim, Min; Lesner, Nicholas P.; Mishra, Prashant; Brabletz, Thomas; Shay, Jerry W.; et al. (Genes & Development, 2019)
Tumors display increased uptake and processing of nutrients to fulfill the demands of rapidly proliferating cancer cells. Seminal studies have shown that the proto-oncogene MYC promotes metabolic reprogramming by altering glutamine uptake and metabolism in cancer cells. How MYC regulates the metabolism of other amino acids in cancer is not fully understood. Using high-performance liquid chromatography (HPLC)-tandem mass spectrometry (LC-MS/MS), we found that MYC increased intracellular levels of tryptophan and tryptophan metabolites in the kynurenine pathway. MYC induced the expression of the tryptophan transporters SLC7A5 and SLC1A5 and the enzyme arylformamidase (AFMID), involved in the conversion of tryptophan into kynurenine. SLC7A5, SLC1A5, and AFMID were elevated in colon cancer cells and tissues, and kynurenine was significantly greater in tumor samples than in the respective adjacent normal tissue from patients with colon cancer. Compared with normal human colonic epithelial cells, colon cancer cells were more sensitive to the depletion of tryptophan. Blocking enzymes in the kynurenine pathway caused preferential death of established colon cancer cells and transformed colonic organoids. We found that only kynurenine and no other tryptophan metabolite promotes the nuclear translocation of the transcription factor aryl hydrocarbon receptor (AHR). Blocking the interaction between AHR and kynurenine with CH223191 reduced the proliferation of colon cancer cells. Therefore, we propose that limiting cellular kynurenine or its downstream targets could present a new strategy to reduce the proliferation of MYC-dependent cancer cells.
CRIS-Team Scopus Importer:2019-09-17
Keywords: AFMID; AHR; cancer; kynurenine; MYC; organoid; SLC1A5; SLC7A5; tryptophan metabolism

Non-redundant functions of EMT transcription factors - Stemmler, Marc; Eccles, Rebecca; Brabletz, Simone; Brabletz, Thomas (Nature Cell Biology, 2019)
Epithelial-mesenchymal transition (EMT) is a crucial embryonic programme that is executed by various EMT transcription factors (EMT-TFs) and is aberrantly activated in cancer and other diseases. However, the causal role of EMT and EMT-TFs in different disease processes, especially cancer and metastasis, continues to be debated. In this Review, we identify and describe specific, non-redundant functions of the different EMT-TFs and discuss the reasons that may underlie disputes about EMT in cancer.
EVALuna2:35254

Oncogenic roles of EMT-inducing transcription factors - Puisieux, Alain; Brabletz, Thomas; Caramel, Julie (Nature Cell Biology, 2014)
The plasticity of cancer cells underlies their capacity to adapt to the selective pressures they encounter during tumour development. Aberrant reactivation of epithelial-mesenchymal transition (EMT), an essential embryonic process, can promote cancer cell plasticity and fuel both tumour initiation and metastatic spread. Here we discuss the roles of EMT-inducing transcription factors in creating a pro-tumorigenic setting characterized by an intrinsic ability to withstand oncogenic insults through the mitigation of p53-dependent oncosuppressive functions and the gain of stemness-related properties.
EVALuna2:10187

Pancreas morphogenesis and homeostasis depends on tightly regulated Zeb1 levels in epithelial cells - Losada, Maria Lasierra; Pauler, Melissa; Vandamme, Niels; Goossens, Steven; Berx, Geert; Leppkes, Moritz; Schuhwerk, Harald; Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc (Cell Death Discovery, 2021)
The pancreas is comprised of exocrine and endocrine compartments releasing digestive enzymes into the duodenum and regulating blood glucose levels by insulin and glucagon release. Tissue homeostasis is depending on transcription factor networks, involving Ptf1α, Ngn3, Nkx6.1, and Sox9, which are already activated during organogenesis. However, proper organ function is challenged by diets of high sugar and fat content, increasing the risk of type 2 diabetes and other disorders. A detailed understanding of processes that are important for homeostasis and are impaired during type 2 diabetes is lacking. Here, we show that Zeb1—a transcription factor known for its pivotal role in epithelial-mesenchymal transition, cell plasticity, and metastasis in cancer—is expressed at low levels in epithelial cells of the pancreas and is crucial for organogenesis and pancreas function. Loss of Zeb1 in these cells result in an increase of islet mass, impaired glucose tolerance, and sensitizes to develop liver and pancreas steatosis during diabetes and obesity. Interestingly, moderate overexpression of Zeb1 results in severe pancreas agenesis and lethality after birth, due to islet insufficiency and lack of acinar structures. We show that Zeb1 induction interferes with proper differentiation, cell survival, and proliferation during pancreas formation, due to deregulated expression of endocrine-specific transcription factors. In summary, our analysis suggests a novel role of Zeb1 for homeostasis in epithelial cells that is indispensable for pancreas morphogenesis and proper organ function involving a tight regulation of Zeb1 expression.
CRIS-Team Scopus Importer:2021-06-18

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Prognostic significance of Zinc finger E-box binding homeobox 1 (ZEB1) expression in cancer cells and cancer-associated fibroblasts in pancreatic head cancer - Bronsert, Peter; Kohler, Ilona; Timme, Sylvia; Kiefer, Selina; Werner, Martin; Schilling, Oliver; Vashist, Yogesh; Makowiec, Frank; Brabletz, Thomas; Hopt, Ulrich T.; Bausch, Dirk; Kulemann, Birte; et al. (Surgery, 2014)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an aggressive biology and poor prognosis. Experimental evidence has suggested a role for the transcriptional repressor Zinc finger E-box binding homeobox 1 (ZEB1) in epithelial-mesenchymal transition, invasion, and metastasis in PDAC. ZEB1 expression has been observed in cancer cells as well as stromal fibroblasts. Our study aimed to evaluate the prognostic value of ZEB1 expression in PDAC tissue.Patient baseline and follow-up data were extracted from a prospectively maintained database. After clinicopathologic re-review, serial sliced tissue slides were immunostained for ZEB1, E-cadherin, vimentin, and pan-cytokeratin. ZEB1 expression in cancer cells and adjacent stromal fibroblasts was graded separately and correlated to routine histopathologic parameters and survival after resection.A total of 117 cases of PDAC were included in the study. High ZEB1 expression in cancer cells and in stromal cancer-associated fibroblasts was associated with poor prognosis. There was also a trend for poor prognosis with a lymph node ratio of greater than 0.10. In line with its role as an inducer of epithelial-mesenchymal transition, ZEB1 expression in cancer cells was positively correlated with Vimentin expression and negatively with E-Cadherin expression. In multivariate analysis, stromal ZEB1 expression grade was the only independent factor of survival after resection.Our data suggest that ZEB1 expression in cancer cells as well as in stromal fibroblasts are strong prognostic factors in PDAC. Stromal ZEB1 expression is identified for the first time as an independent predictor of survival after resection of PDAC. This observation suggests that therapies targeting ZEB1 and its downstream pathways could hit both cancer cells and supporting cancer-associated fibroblasts.
EVALuna2:10194

Road to perdition: Zeb1-dependent and -independent ways to metastasis - Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc (Cell Cycle, 2017)
EVALuna2:10234

Stress-induced cleavage of Myc promotes cancer cell survival - Conacci-Sorrell, Maralice; Ngouenet, Celine; Anderson, Sarah; Brabletz, Thomas; Eisenman, Robert N. (Genes & Development, 2014)
Evasion of apoptosis is critical in Myc-induced tumor progression. Here we report that cancer cells evade death under stress by activating calpain-mediated proteolysis of Myc. This generates Myc-nick, a cytoplasmic, transcriptionally inactive cleavage product of Myc. We found conversion of Myc into Myc-nick in cell lines and tissues derived from multiple cancers. In colon cancer, the production of Myc-nick is enhanced under stress conditions such as hypoxia and nutrient deprivation. Under these conditions, ectopic expression of Myc-nick promotes anchorage-independent growth and cell survival at least in part by promoting autophagy. Myc-nick also delays colon cancer cell death after treatment with chemotherapeutic drugs such as etoposide, cisplatin, and imatinib. Furthermore, colon cancer cells expressing a cleavage-resistant form of Myc undergo extensive apoptosis but are rescued by overexpression of Myc-nick. We also found that ectopic expression of Myc-nick results in the induction of the actin-bundling protein fascin, formation of filopodia, and increased cell motility-all mediators of tumor metastasis. Myc-nick-induced survival, autophagy, and motility require Myc box II (MBII), a region of Myc-nick that recruits acetyltransferases that in turn modify cytoplasmic proteins, including ?-tubulin and ATG3. Our results suggest that Myc-nick-induced survival and motility contribute to colon cancer progression and metastasis.
EVALuna2:10185

Targeting EMT in Cancer with Repurposed Metabolic Inhibitors - Ramesh, Vignesh; Brabletz, Thomas; Ceppi, Paolo (Trends in Cancer, 2020)
Epithelial-to-mesenchymal transition (EMT) determines the most lethal features of cancer, metastasis formation and chemoresistance, and therefore represents an attractive target in oncology. However, direct targeting of EMT effector molecules is, in most cases, pharmacologically challenging. Since emerging research has highlighted the distinct metabolic circuits involved in EMT, we propose the use of metabolism-specific inhibitors, FDA approved or under clinical trials, as a drug repurposing approach to target EMT in cancer. Metabolism-inhibiting drugs could be coupled with standard chemo- or immunotherapy to combat EMT-driven resistant and aggressive cancers.
CRIS-Team Scopus Importer:2020-07-24
Keywords: chemoresistance; drug repurposing; epithelial–mesenchymal transition; metabolic inhibitor; partial EMT

The AHR target gene scinderin activates the WNT pathway by facilitating the nuclear translocation of β-catenin - Perez-Castro, Lizbeth; Venkateswaran, Niranjan; Garcia, Roy; Hao, Yi Heng; Lafita-Navarro, M. C.; Kim, Jiwoong; Segal, Dagan; Saponzik, Etai; Chang, Bo Jui; Fiolka, Reto; Danuser, Gaudenz; Xu, Lin; et al. (Journal of Cell Science, 2022)
The ligand-activated transcription factor aryl hydrocarbon receptor (AHR) regulates cellular detoxification, proliferation and immune evasion in a range of cell types and tissues, including cancer cells. In this study, we used RNA-sequencing to identify the signature of the AHR target genes regulated by the pollutant 2,3,7,8-tetrachlorodibenzodioxin (TCDD) and the endogenous ligand kynurenine (Kyn), a tryptophan-derived metabolite. This approach identified a signature of six genes (CYP1A1, ALDH1A3, ABCG2, ADGRF1 and SCIN) as commonly activated by endogenous or exogenous ligands of AHR in multiple colon cancer cell lines. Among these, the actin-severing protein scinderin (SCIN) was necessary for cell proliferation; SCIN downregulation limited cell proliferation and its expression increased it. SCIN expression was elevated in a subset of colon cancer patient samples, which also contained elevated β-catenin levels. Remarkably, SCIN expression promoted nuclear translocation of β-catenin and activates the WNT pathway. Our study identifies a new mechanism for adhesion-mediated signaling in which SCIN, likely via its ability to alter the actin cytoskeleton, facilitates the nuclear translocation of β-catenin.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Aryl hydrocarbon receptor; Colon cancer; FICZ; Kynurenine; TCDD

The aryl hydrocarbon receptor regulates nucleolar activity and protein synthesis in MYC-expressing cells - Lafita-Navarro, M. Carmen; Kim, Min; Borenstein-Auerbach, Nofit; Venkateswaran, Niranjan; Hao, Yi-Heng; Ray, Roshni; Brabletz, Thomas; Scaglioni, Pier Paolo; Shay, Jerry W.; Conacci-Sorrell, Maralice (Genes & Development, 2018)
MYC enhances protein synthesis by regulating genes involved in ribosome biogenesis and protein translation. Here, we show that MYC-induced protein translation is mediated by the transcription factor aryl hydrocarbon receptor (AHR), which is induced by MYC in colonic cells. AHR promotes protein synthesis by activating the transcription of genes required for ribosome biogenesis and protein translation, including OGFOD1 and NOLC1. Using surface sensing of translation (SUnSET) to measure global protein translation, we found that silencing AHR or its targets diminishes protein synthesis. Therefore, targeting AHR or its downstream pathways could provide a novel approach to limit biomass production in MYC-driven tumors.
EVALuna2:34671

The collagen‐modifying enzyme plod2 is induced and required during l1‐mediated colon cancer progression - Cheriyamundath, Sanith; Kumar, Anmol; Gavert, Nancy; Brabletz, Thomas; Ben‐ze’ev, Avri (International Journal of Molecular Sciences, 2021)
The overactivation of Wnt/β‐catenin signaling is a hallmark of colorectal cancer (CRC) development. We identified the cell adhesion molecule L1CAM (L1) as a target of β‐catenin‐TCF transactivation in CRC cells. The overexpression of L1 in CRC cells confers enhanced proliferation, motility, tumorigenesis and liver metastasis, and L1 is exclusively localized in the invasive areas of human CRC tissue. A number of genes are induced after L1 transfection into CRC cells by a mechanism involving the cytoskeletal protein ezrin and the NF‐ĸB pathway. When studying the changes in gene expression in CRC cells overexpressing L1 in which ezrin levels were suppressed by shRNA to ezrin, we discovered the collagen‐modifying enzyme lysyl hydroxylase 2 (PLOD2) among these genes. We found that increased PLOD2 expression was required for the cellular processes conferred by L1, including enhanced proliferation, motility, tumorigenesis and liver metastasis, since the suppression of endogenous PLOD2 expression, or its enzymatic activity, blocked the enhanced tumor-igenic properties conferred by L1. The mechanism involved in increased PLOD2 expression by L1 involves ezrin signaling and PLOD2 that affect the SMAD2/3 pathway. We found that PLOD2 is localized in the colonic crypts in the stem cell compartment of the normal mucosa and is found at increased levels in invasive areas of the tumor and, in some cases, throughout the tumor tissue. The therapeutic strategies to target PLOD2 expression might provide a useful approach for CRC treat-ment.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Colonic crypts; Colorectal cancer; Ezrin; Invasion and metastasis; L1; Lysyl hydroxylase 2; PLOD2

The EMT-activator ZEB1 induces bone metastasis associated genes including BMP-inhibitors - Mock, Kerstin; Preca, Bogdan-Tiberius; Brummer, Tilman; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (Oncotarget, 2015)
Tumor cell invasion, dissemination and metastasis is triggered by an aberrant activation of epithelial-to-mesenchymal transition (EMT), often mediated by the transcription factor ZEB1. Disseminating tumor cells must acquire specific features that allow them to colonize at different organ sites. Here we identify a set of genes that is highly expressed in breast cancer bone metastasis and activated by ZEB1. This gene set includes various secreted factors, e.g. the BMP-inhibitor FST, that are described to reorganize the bone microenvironment. By inactivating BMP-signaling, BMP-inhibitors are well-known to induce osteolysis in development and disease. We here demonstrate that the expression of ZEB1 and BMP-inhibitors is correlated with bone metastasis, but not with brain or lung metastasis of breast cancer patients. In addition, we show that this correlated expression pattern is causally linked, as ZEB1 induces the expression of the BMP-inhibitors NOG, FST and CHRDL1 both by directly increasing their gene transcription, as well as by indirectly suppressing their reduction via miR-200 family members. Consequently, ZEB1 stimulates BMP-inhibitor mediated osteoclast differentiation. These findings suggest that ZEB1 is not only driving EMT, but also contributes to the formation of osteolytic bone metastases in breast cancer.
EVALuna2:10197

The EMT-activator Zeb1 is a key factor for cell plasticity and promotes metastasis in pancreatic cancer - Krebs, Angela M.; Mitschke, Julia; Losada, Maria Lasierra; Schmalhofer, Otto; Boerries, Melanie; Busch, Hauke; Böttcher, Martin; Mougiakakos, Dimitrios; Reichardt, Wilfried; Bronsert, Peter; Brunton, Valerie G.; Pilarsky, Christian; et al. (Nature Cell Biology, 2017)
Metastasis is the major cause of cancer-associated death. Partial activation of the epithelial-to-mesenchymal transition program (partial EMT) was considered a major driver of tumour progression from initiation to metastasis. However, the role of EMT in promoting metastasis has recently been challenged, in particular concerning effects of the Snail and Twist EMT transcription factors (EMT-TFs) in pancreatic cancer. In contrast, we show here that in the same pancreatic cancer model, driven by Pdx1-cre-mediated activation of mutant Kras and p53 (KPC model), the EMT-TF Zeb1 is a key factor for the formation of precursor lesions, invasion and notably metastasis. Depletion of Zeb1 suppresses stemness, colonization capacity and in particular phenotypic/metabolic plasticity of tumour cells, probably causing the observed in vivo effects. Accordingly, we conclude that different EMT-TFs have complementary subfunctions in driving pancreatic tumour metastasis. Therapeutic strategies should consider these potential specificities of EMT-TFs to target these factors simultaneously.

The EMT transcription factor ZEB1 blocks osteoblastic differentiation in bone development and osteosarcoma - Ruh, Manuel; Stemmler, Marc; Frisch, Isabell; Fuchs, Kathrin; van Roey, Ruthger; Kleemann, Julia; Roas, Maike; Schuhwerk, Harald; Eccles, Rebecca; Agaimy, Abbas; Baumhoer, Daniel; Berx, Geert; et al. (Journal of Pathology, 2021)
Osteosarcoma is an often-fatal mesenchyme-derived malignancy in children and young adults. Overexpression of EMT-transcription factors (EMT-TFs) has been associated with poor clinical outcome. Here, we demonstrated that the EMT-TF ZEB1 is able to block osteoblastic differentiation in normal bone development as well as in osteosarcoma cells. Consequently, overexpression of ZEB1 in osteosarcoma characterizes poorly differentiated, highly metastatic subgroups and its depletion induces differentiation of osteosarcoma cells. Overexpression of ZEB1 in osteosarcoma is frequently associated with silencing of the imprinted DLK-DIO3 locus, which encodes for microRNAs targeting ZEB1. Epigenetic reactivation of this locus in osteosarcoma cells reduces ZEB1 expression, induces differentiation, and sensitizes to standard treatment, thus indicating therapeutic options for ZEB1-driven osteosarcomas. (c) 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team WoS Importer:2021-05-14

The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

The intestinal stem cell regulating gene ASCL2 is required for L1-mediated colon cancer progression - Basu, Sayon; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Cancer Letters, 2018)
Aberrant Wnt/β-catenin signaling is a common event during human colorectal cancer (CRC) development. Previously, we characterized members of the L1 family of cell adhesion receptors as targets of β-catenin-LEF1/TCF transactivation that are expressed at the invasive CRC tissue edge. Overexpression of L1 in CRC cells confers enhanced motility, tumorigenesis and liver metastasis. We identified several downstream targets of L1-mediated signaling that are considered key intestinal stem cell signature genes. Here, we investigated the involvement of ASCL2, a Wnt target gene and key determinant of intestinal stem cell state, in L1-mediated CRC progression. In L1 overexpressing CRC cells we found an increase in ASCL2, a decrease in E-cadherin and accumulation of nuclear β-catenin, β-catenin-LEF1/TCF transactivation and target gene expression. The increase in ASCL2 by L1 overexpression enhanced ASCL2 target gene expression, conferred increased motility, tumorigenesis and metastasis, similar to L1 overexpression. Suppression of ASCL2 in cells expressing L1 blocked these tumorigenic properties. In human CRC tissue, ASCL2 was detected in the nuclei of cells at invasive areas of the tumor that also expressed L1. The results suggest that increased ASCL2 expression is a critical step in L1-mediated CRC progression.
EVALuna2:34143

The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19

The transcription factor ZEB1 regulates stem cell self-renewal and cell fate in the adult hippocampus - Gupta, Bhavana; Errington, Adam C.; Jimenez-Pascual, Ana; Eftychidis, Vasileios; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas; Petrik, David; Siebzehnrubl, Florian A. (Cell Reports, 2021)
Radial glia-like (RGL) stem cells persist in the adult mammalian hippocampus, where they generate new neurons and astrocytes throughout life. The process of adult neurogenesis is well documented, but cell-autonomous factors regulating neuronal and astroglial differentiation are incompletely understood. Here, we evaluate the functions of the transcription factor zinc-finger E-box binding homeobox 1 (ZEB1) in adult hippocampal RGL cells using a conditional-inducible mouse model. We find that ZEB1 is necessary for self-renewal of active RGL cells. Genetic deletion of Zeb1 causes a shift toward symmetric cell division that consumes the RGL cell and generates pro-neuronal progenies, resulting in an increase of newborn neurons and a decrease of newly generated astrocytes. We identify ZEB1 as positive regulator of the ets-domain transcription factor ETV5 that is critical for asymmetric division.
CRIS-Team WoS Importer:2021-09-03

The Wnt Target Gene L1 in Colon Cancer Invasion and Metastasis - Haase, Gal; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Cancers, 2016)
The Wnt-?-catenin signaling pathway is highly conserved during evolution and determines normal tissue homeostasis. Hyperactivation of Wnt-?-catenin signaling is a characteristic feature of colorectal cancer (CRC) development. ?-catenin is a major transducer of the Wnt signal from the cytoplasm into the nucleus where it acts as a co-transcriptional activator of ?-catenin-TCF target genes. ?-catenin is also required for linking cadherin type cell-cell adhesion receptors to the cytoskeleton, and consequently Wnt-?-catenin signaling is an attractive system for investigating the role of adhesion-mediated signaling in both normal intestinal tissue homeostasis and CRC development. In this review, we summarize our studies on one Wnt-?-catenin target gene, L1, a member of the immunoglobulin-like cell adhesion transmembrane receptor family. We describe the mechanisms of L1-mediated signaling in CRC cells, its exclusive localization in invasive areas of CRC tissue, and its ability to increase cell motility and confer metastasis to the liver. We discuss the activation (by L1) of genes via an ezrin-NF-?B pathway and the induction of genes also found in the intestinal stem cell signature. By studying L1 (adhesion)-mediated signaling, we expect to learn about mechanisms regulating both normal intestinal homeostasis and CRC development.
EVALuna2:10215

The ZEB1/miR-200c feedback loop regulates invasion via actin interacting proteins MYLK and TKS5 - Sundararajan, Vignesh; Gengenbacher, Nicolas; Stemmler, Marc; Kleemann, Julia; Brabletz, Thomas; Brabletz, Simone (Oncotarget, 2015)
Epithelial to mesenchymal transition (EMT) is a developmental process which is aberrantly activated during cancer invasion and metastasis. Elevated expression of EMT-inducers like ZEB1 enables tumor cells to detach from the primary tumor and invade into the surrounding tissue. The main antagonist of ZEB1 in controlling EMT is the microRNA-200 family that is reciprocally linked to ZEB1 in a double negative feedback loop. Here, we further elucidate how the ZEB1/miR-200 feedback loop controls invasion of tumor cells. The process of EMT is attended by major changes in the actin cytoskeleton. Via in silico screening of genes encoding for actin interacting proteins, we identified two novel targets of miR-200c - TKS5 and MYLK (MLCK). Co-expression of both genes with ZEB1 was observed in several cancer cell lines as well as in breast cancer patients and correlated with low miR-200c levels. Depletion of TKS5 or MYLK in breast cancer cells reduced their invasive potential and their ability to form invadopodia. Whereas TKS5 is known to be a major component, we could identify MYLK as a novel player in invadopodia formation. In summary, TKS5 and MYLK represent two mediators of invasive behavior of cancer cells that are regulated by the ZEB1/miR-200 feedback loop.
EVALuna2:10204

Thymidylate synthase is functionally associated with ZEB1 and contributes to the epithelial-to-mesenchymal transition of cancer cells - Siddiqui, Aarif; Vazakidou, Maria Eleni; Schwab, Annemarie; Napoli, Francesca; Fernandez-Molina, Cristina; Rapa, Ida; Stemmler, Marc; Volante, Marco; Brabletz, Thomas; Ceppi, Paolo (Journal of Pathology, 2017)
Thymidylate synthase (TS) is a fundamental enzyme of nucleotide metabolism and one of the oldest anti-cancer targets. Beginning from the analysis of gene array data from the NCI-60 panel of cancer cell lines, we identified a significant correlation at both gene and protein level between TS and the markers of epithelial-to-mesenchymal transition (EMT), a developmental process that allows cancer cells to acquire features of aggressiveness, like motility and chemoresistance. TS levels were found to be significantly augmented in mesenchymal-like compared to epithelial-like cancer cells, to be regulated by EMT induction, and to negatively correlate with micro-RNAs (miRNAs) usually expressed in epithelial-like cells and known to actively suppress EMT. Transfection of EMT-suppressing miRNAs reduced TS levels, and a specific role for miR-375 in targeting the TS 3'-untranslated region was identified. A particularly relevant association was found between TS and the powerful EMT driver ZEB1, the shRNA-mediated knockdown of which up-regulated miR-375 and reduced TS cellular levels. The TS-ZEB1 association was confirmed in clinical specimens from lung tumours and in a genetic mouse model of pancreatic cancer with ZEB1 deletion. Interestingly, TS itself appeared to have a regulatory role in EMT in cancer cells, as TS knockdown could directly reduce the EMT phenotype, the migratory ability of cells, the expression of stem-like markers, and chemoresistance. Taken together, these data indicate that the TS enzyme is functionally linked with EMT and cancer differentiation, with several potential translational implications. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:10226

Tumor cell heterogeneity in Small Cell Lung Cancer (SCLC): phenotypical and functional differences associated with Epithelial-Mesenchymal Transition (EMT) and DNA methylation changes - Krohn, Alexander; Ahrens, Theresa; Yalcin, Arzu; Ploenes, Till; Wehrle, Julius; Taromi, Sanaz; Wollner, Stefan; Follo, Marie; Brabletz, Thomas; Mani, Sendurai A.; Claus, Rainer; Hackanson, Bjoern; et al. (PLoS ONE, 2014)
Small Cell Lung Cancer (SCLC) is a specific subtype of lung cancer presenting as highly metastatic disease with extremely poor prognosis. Despite responding initially well to chemo- or radiotherapy, SCLC almost invariably relapses and develops resistance to chemotherapy. This is suspected to be related to tumor cell subpopulations with different characteristics resembling stem cells. Epithelial-Mesenchymal Transition (EMT) is known to play a key role in metastatic processes and in developing drug resistance. This is also true for NSCLC, but there is very little information on EMT processes in SCLC so far. SCLC, in contrast to NSCLC cell lines, grow mainly in floating cell clusters and a minor part as adherent cells. We compared these morphologically different subpopulations of SCLC cell lines for EMT and epigenetic features, detecting significant differences in the adherent subpopulations with high levels of mesenchymal markers such as Vimentin and Fibronectin and very low levels of epithelial markers like E-cadherin and Zona Occludens 1. In addition, expression of EMT-related transcription factors such as Snail/Snai1, Slug/Snai2, and Zeb1, DNA methylation patterns of the EMT hallmark genes, functional responses like migration, invasion, matrix metalloproteases secretion, and resistance to chemotherapeutic drug treatment all differed significantly between the sublines. This phenotypic variability might reflect tumor cell heterogeneity and EMT during metastasis in vivo, accompanied by the development of refractory disease in relapse. We propose that epigenetic regulation plays a key role during phenotypical and functional changes in tumor cells and might therefore provide new treatment options for SCLC patients.
EVALuna2:10195

Upholding a role for EMT in breast cancer metastasis - Ye, Xin; Brabletz, Thomas; Kang, Yibin; Longmore, Gregory D.; Angela Nieto, M.; Stanger, Ben Z.; Yang, Jing; Weinberg, Robert A. (Nature, 2017)
EVALuna2:10232

Upholding a role for EMT in pancreatic cancer metastasis - Aiello, Nicole M.; Brabletz, Thomas; Kang, Yibin; Angela Nieto, M.; Weinberg, Robert A.; Stanger, Ben Z. (Nature, 2017)
EVALuna2:10233

ZEB1-associated drug resistance in cancer cells is reversed by the class I HDAC inhibitor mocetinostat - Meidhof, Simone; Brabletz, Simone; Lehmann, Waltraut; Preca, Bogdan-Tiberius; Mock, Kerstin; Ruh, Manuel; Schueler, Julia; Berthold, Maria; Weber, Anika; Burk, Ulrike; Luebbert, Michael; Puhr, Martin; et al. (Embo Molecular Medicine, 2015)
Therapy resistance is a major clinical problem in cancer medicine and crucial for disease relapse and progression. Therefore, the clinical need to overcome it, particularly for aggressive tumors such as pancreatic cancer, is very high. Aberrant activation of an epithelial-mesenchymal transition (EMT) and an associated cancer stem cell phenotype are considered a major cause of therapy resistance. Particularly, the EMT-activator ZEB1 was shown to confer stemness and resistance. We applied a systematic, stepwise strategy to interfere with ZEB1 function, aiming to overcome drug resistance. This led to the identification of both its target gene miR-203 as a major drug sensitizer and subsequently the class I HDAC inhibitor mocetinostat as epigenetic drug to interfere with ZEB1 function, restore miR-203 expression, repress stemness properties, and induce sensitivity against chemotherapy. Thereby, mocetinostat turned out to be more effective than other HDAC inhibitors, such as SAHA, indicating the relevance of the screening strategy. Our data encourage the application of mechanism-based combinations of selected epigenetic drugs with standard chemotherapy for the rational treatment of aggressive solid tumors, such as pancreatic cancer.
EVALuna2:10188

ZEB1 becomes a transcriptional activator upon interacting with YAP - Lehmann, W.; Eccles, Rebecca; Kleemann, Julia; Mossmann, D.; Meisinger, C.; Mahadevan, V.; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (2017)
EVALuna2:35505

Zeb1 modulates hematopoietic stem cell fates required for suppressing acute myeloid leukemia - Almotiri, Alhomidi; Alzahrani, Hamed; Menendez-Gonzalez, Juan Bautista; Abdelfattah, Ali; Alotaibi, Badi; Saleh, Lubaid; Greene, Adelle; Georgiou, Mia; Gibbs, Alex; Alsayari, Amani; Taha, Sarab; Thomas, Leigh Anne; et al. (Journal of Clinical Investigation, 2021)
Zeb1, a zinc finger E-box binding homeobox epithelial-mesenchymal transition (EMT) transcription factor, confers properties of "stemness,"such as self-renewal, in cancer. Yet little is known about the function of Zeb1 in adult stem cells. Here, we used the hematopoietic system as a well-established paradigm of stem cell biology to evaluate Zeb1-mediated regulation of adult stem cells. We employed a conditional genetic approach using the Mx1-Cre system to specifically knock out (KO) Zeb1 in adult hematopoietic stem cells (HSCs) and their downstream progeny. Acute genetic deletion of Zeb1 led to rapid-onset thymic atrophy and apoptosis-driven loss of thymocytes and T cells. A profound cell-autonomous self-renewal defect and multilineage differentiation block were observed in Zeb1-KO HSCs. Loss of Zeb1 in HSCs activated transcriptional programs of deregulated HSC maintenance and multilineage differentiation genes and of cell polarity consisting of cytoskeleton-, lipid metabolism/lipid membrane-, and cell adhesion-related genes. Notably, epithelial cell adhesion molecule (EpCAM) expression was prodigiously upregulated in Zeb1-KO HSCs, which correlated with enhanced cell survival, diminished mitochondrial metabolism, ribosome biogenesis, and differentiation capacity and an activated transcriptomic signature associated with acute myeloid leukemia (AML) signaling. ZEB1 expression was downregulated in AML patients, and Zeb1 KO in the malignant counterparts of HSCs - leukemic stem cells (LSCs) - accelerated MLL-AF9- and Meis1a/Hoxa9-driven AML progression, implicating Zeb1 as a tumor suppressor in AML LSCs. Thus, Zeb1 acts as a transcriptional regulator in hematopoiesis, critically coordinating HSC self-renewal, apoptotic, and multilineage differentiation fates required to suppress leukemic potential in AML.
CRIS-Team Scopus Importer:2021-01-15

ZEB1 turns into a transcriptional activator by interacting with YAP1 in aggressive cancer types - Lehmann, Waltraut; Mossmann, Dirk; Kleemann, Julia; Mock, Kerstin; Meisinger, Chris; Brummer, Tilman; Herr, Ricarda; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (Nature Communications, 2016)
Early dissemination, metastasis and therapy resistance are central hallmarks of aggressive cancer types and the leading cause of cancer-associated deaths. The EMT-inducing transcriptional repressor ZEB1 is a crucial stimulator of these processes, particularly by coupling the activation of cellular motility with stemness and survival properties. ZEB1 expression is associated with aggressive behaviour in many tumour types, but the potent effects cannot be solely explained by its proven function as a transcriptional repressor of epithelial genes. Here we describe a direct interaction of ZEB1 with the Hippo pathway effector YAP, but notably not with its paralogue TAZ. In consequence, ZEB1 switches its function to a transcriptional co-activator of a 'common ZEB1/YAP target gene set', thereby linking two pathways with similar cancer promoting effects. This gene set is a predictor of poor survival, therapy resistance and increased metastatic risk in breast cancer, indicating the clinical relevance of our findings.
EVALuna2:10213

ZIP4 Increases Expression of Transcription Factor ZEB1 to Promote Integrin α3β1 Signaling and Inhibit Expression of the Gemcitabine Transporter ENT1 in Pancreatic Cancer Cells - Liu, Mingyang; Zhang, Yuqing; Yang, Jingxuan; Cui, Xiaobo; Zhou, Zhijun; Zhan, Hanxiang; Ding, Kai; Tian, Xiang; Yang, Zhibo; Fung, Kar Ming A.; Edil, Barish H.; Postier, Russell G.; et al. (Gastroenterology, 2020)
Background & Aims: Pancreatic tumors undergo rapid growth and progression, become resistant to chemotherapy, and recur after surgery. We studied the functions of the solute carrier family 39 member 4 (SLC39A4, also called ZIP4), which regulates concentrations of intracellular zinc and is increased in pancreatic cancer cells, in cell lines and mice. Methods: We obtained 93 pancreatic cancer specimens (tumor and adjacent nontumor tissues) from patients who underwent surgery and gemcitabine chemotherapy and analyzed them by immunohistochemistry. ZIP4 and/or ITGA3 or ITGB1 were overexpressed or knocked down with short hairpin RNAs in AsPC-1 and MIA PaCa-2 pancreatic cancer cells lines, and in pancreatic cells from KPC and KPC-ZEB1–knockout mice, and pancreatic spheroids were established; cells and spheroids were analyzed by immunoblots, reverse transcription polymerase chain reaction, and liquid chromatography tandem mass spectrometry. We studied transcriptional regulation of ZEB1, ITGA3, ITGB1, JNK, and ENT1 by ZIP4 using chromatin precipitation and luciferase reporter assays. Nude mice were given injections of genetically manipulated AsPC-1 and MIA PaCa-2 cells, and growth of xenograft tumors and metastases was measured. Results: In pancreatic cancer specimens from patients, increased levels of ZIP4 were associated with shorter survival times. MIA PaCa-2 cells that overexpressed ZIP4 had increased resistance to gemcitabine, 5-fluorouracil, and cisplatin, whereas AsPC-1 cells with ZIP4 knockdown had increased sensitivity to these drugs. In mice, xenograft tumors grown from AsPC-1 cells with ZIP4 knockdown were smaller and more sensitive to gemcitabine. ZIP4 overexpression significantly reduced accumulation of gemcitabine in pancreatic cancer cells, increased growth of xenograft tumors in mice, and increased expression of the integrin subunits ITGA3 and ITGB1; expression levels of ITGA3 and ITGB1 were reduced in cells with ZIP4 knockdown. Pancreatic cancer cells with ITGA3 or ITGB1 knockdown had reduced proliferation and formed smaller tumors in mice, despite overexpression of ZIP4; spheroids established from these cells had increased sensitivity to gemcitabine. We found ZIP4 to activate STAT3 to induce expression of ZEB1, which induced expression of ITGA3 and ITGB1 in KPC cells. Increased ITGA3 and ITGB1 expression and subsequent integrin α3β1 signaling, via c-Jun-N-terminal kinase (JNK), inhibited expression of the gemcitabine transporter ENT1, which reduced gemcitabine uptake by pancreatic cancer cells. ZEB1-knockdown cells had increased sensitivity to gemcitabine. Conclusions: In studies of pancreatic cancer cell lines and mice, we found that ZIP4 increases expression of the transcription factor ZEB1, which activates expression of ITGA3 and ITGB1. The subsequent increase in integrin α3β1 signaling, via JNK, inhibits expression of the gemcitabine transporter ENT1, so that cells take up smaller amounts of the drug. Activation of this pathway might help mediate resistance of pancreatic tumors to chemotherapeutic agents.
CRIS-Team Scopus Importer:2020-02-11
Keywords: EMT; Oncogene; Pancreas; Signal Transduction